2001
DOI: 10.1046/j.0953-816x.2001.01564.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterned cerebellar Purkinje cell death in a transgenic mouse model of Niemann Pick type A/B disease

Abstract: Niemann Pick disease is a family of autosomal recessive disorders characterized by cholesterol accumulation. The most common type is Niemann Pick type A/B (NPA/B), resulting from deficient acid sphingomyelinase activity, which leads to sphingomyelin and cholesterol accumulation. The neuropathology of NPA/B includes widespread neuronal degeneration. An acid sphingomyelinase knockout mouse model of NPA/B (ASMKO) has been developed by the targeted deletion of the acid sphingomyelinase gene. When cerebellar morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 47 publications
10
67
0
Order By: Relevance
“…Three central bands of resistant cells and preferential loss of Purkinje cells in the anterior cerebellum with sparing of lobe X have been described in the leaner mutant (Herrup and Wilczynski, 1982) and in the mouse models of NiemannPick disease types A/B [acid sphingomyelinase knock-out (ASMKO)] and C (Higashi et al, 1993;Sarna et al, 2001). These changes are preceded by granule cell loss in the leaner mouse (Herrup and Wilczynski, 1982;Heckroth and Abbott, 1994), distinguishing the pathological findings from those seen in robotic mutants.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Three central bands of resistant cells and preferential loss of Purkinje cells in the anterior cerebellum with sparing of lobe X have been described in the leaner mutant (Herrup and Wilczynski, 1982) and in the mouse models of NiemannPick disease types A/B [acid sphingomyelinase knock-out (ASMKO)] and C (Higashi et al, 1993;Sarna et al, 2001). These changes are preceded by granule cell loss in the leaner mouse (Herrup and Wilczynski, 1982;Heckroth and Abbott, 1994), distinguishing the pathological findings from those seen in robotic mutants.…”
Section: Discussionmentioning
confidence: 94%
“…These changes are preceded by granule cell loss in the leaner mouse (Herrup and Wilczynski, 1982;Heckroth and Abbott, 1994), distinguishing the pathological findings from those seen in robotic mutants. However, the similarity of the region-specific cell loss in robotic mice to the Niemann-Pick models is more striking, and dot-like ubiquitin staining has also been noted in the type C disease model (Higashi et al, 1993;Sarna et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…An absence or deficiency of functional ASM protein results in lysosomal accumulation of sphingomyelin, and subsequent secondary metabolic defects such as abnormal cholesterol accumulation (7,20). Cholesterol buildup in the ASMKO mouse brain can be visualized by using filipin, an autofluorescent molecule isolated from Streptomyces filipinensis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown zebrin II IHC to be a powerful tool. Its expression reflects the fundamental molecular architecture of the cerebellum and is sensitive to genetic manipulations of cerebellar development [e.g., Lc/ϩ (Tano et al 1992); weaver (Eisenman et al 1998); disabled (Gallagher et al Figure 3) or patterns of Purkinje cell death [e.g., the acid sphingomyelinase null (ASMKO) mouse (Sarna et al 2001)] but insensitive to secondary influences such as general health status, age, or gender. It is highly reproducible among individuals, is insensitive to the genetic background against which a mutation is seen, and is accurately quantifiable, both for the number of stripes and their widths.…”
Section: Discussionmentioning
confidence: 99%